Perancangan Mesin CNC untuk Pengerjaan Logam Aluminium dan Carbon Steel - Ridwan Ridwan; Wakhid Utomo; Oki Yosevi (Politeknik Negeri Batam, 2022)
Generally, in the industry many use CNC (Computer Numerically Control) machines that can process heavy metal work such as carbon steel. It's just that its use requires a very large cost. To overcome this, it is necessary to design a CNC router type machine for aluminum and carbon steel metalworking which will be operated at PT. XYZ, in order to increase production efficiency with relatively little cost. Currently, the company has a CNC router type that is only capable of processing resin, Bakelite, durostone and recocel materials, and for working on aluminum and carbon steel materials still used conventional milling machine. In this research, the design and manufacture of a 3 axis CNC router machine that can process AISI 1046 carbon steel metal material and can be produced by yourself is carried out. The method used is to design the structure of the machine, and to select a stepper motor as the driving force for the x, y and z axes. The results of this study obtained a 3 axis CNC router machine with electronic components that have been determined, so that the design torque of the stepper motor is 2.8 Nm. The CNC router machine that has been designed is capable of working on AISI 1046 carbon steel metal. In the experimental process the depth of food is using 0.2 - 1 mm/turn with a feedrate of 200 mm/minute. The measurement results of the test object from the designed CNC router machining process do not exceed 0.2 mm. And the measurement results of the test object have met the Japanese Industrial Standards (JIS) tolerance standard with the coordinate measuring machine (CMM) measurement method.